Bisnis Jaringan Internet Fiber Optic di Era Digitalisasi untuk Pemerataan Infrastruktur Telekomunikasi - Insani, Khaerul; Alijoyo, Fransciskus Antonius (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Internet Service Provider (ISP) is a company that provides internet access to end users and is also a promising business opportunity in the digital era. However, the problem of uneven distribution of fiber optic-based internet network infrastructure in society is one of the core problems in this research so that people are limited and cannot enjoy fiber optic-based internet connections in certain areas to support productivity in the digitalized world. To deal with this problem, the solution is Infrastructure Development. Investment in developing fiber optic infrastructure in unreached areas by building Fiber Optic-based internet technology infrastructure. Meanwhile, qualitative method research is based on existing problems. The results of this research aim to evaluate how FTTH (Fiber to the home) technology can be used to improve internet access in various regions, including underserved areas. With the presence of an internet network business based on FTTH (Fiber to the home) technology in society, it is hoped that equal distribution of telecommunications infrastructure can be achieved so that people can enjoy fast, cheap and stable internet services.